(3GdYbhO GdeLhgQI hGddBdj GdeHJcQIs - (3eMeO Hf YeQ Hf bGSe Hf ESeGYjd GdHbQj,J (B1111 (3g` s ((3eOQSI GdeQLGfjI HHZOGO s)
(3ChdgG (B:s
(3hHYO agPG TQM dWja hVYJg Ydi GdQSGdI GdoeSeGI HGdbhGYO GdebQQI hGdahGFO GdeMQQI GdTgjQ HGdHbQjI s
(3BNQgG (B:s
(3ef Ggd gPG GdejOGf hCYhP HGddg ef GdRjGOI hGdfbUGf hCQLhG eef EWdY ajg Ydi gahI ef GdgeRGJ Gf jUdMgG s
(3GdbhGYO GdebQQI hGdahGFO GdeMQQI GdTgjQI H`(B"(3GdHbQjI ai CUhd GdbQGA GdSHYI(B"s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B89s
Keywords: (3GdbQGAGJ hGdJLhjOs